A review on stress determination and control in metal-based additive manufacturing. Issue 1 (January 2023) - Luo, Haoyang; Sun, Xing; Xu, Le; He, Wei; Liang, Xiaoyu
Highlights: An overview of state-of-the-art problems of residual stress in AM with an emphasis on measurement/control methods is presented. Advances in both experimental and numerical investigations regarding residual stress characterization are discussed. Insights on the research opportunities and challenges concerning residual stress in AM are provided. Abstract: Metal additive manufacturing (MAM) is an emerging and disruptive technology that builds three-dimensional (3D) components by adding layer-upon-layer of metallic materials. The complex cyclic thermal history and highly localized energy can produce large temperature gradients, which will, in turn, lead to compressive and tensile stress during the MAM process and eventually result in residual stress. Being an issue of great concern, residual stress, which can cause distortion, delamination, cracking, etc., is considered a key mechanical quantity that affects the manufacturing quality and service performance of MAM parts. In this review paper, the ongoing work in the field of residual stress determination and control for MAM is described with a particular emphasis on the experimental measurement/control methods and numerical models. We also provide insight on what still requires to be achieved and the research opportunities and challenges.